STUDI KOMPARATIF : PERAWATAN LUKA KONVENSIONAL DAN MODERN DI BEKASI - Asih Minarningtyas; Abdul Musyfiq Al-ay Tami (Jurnal Gema Keperawatan, 2018)
This comparative research study compares conventional and modern wound care. The purpose of this study was to improve patient experience, comfort level, family expectations, and system support in using conventional and modern wound care models. This study uses a comparative design. Data collection was done by in-depth interviews (in-depth interviews, observations, and documentation studies. Verbatim results were analyzed by the Colaizzi method. The study took place from August to October 2014. Determination of participants with case design groups of 5 participants from participants who used modern wound care models and 5 participants from participants who used conventional wound care models The theme of the research found was the experience of informants carrying out conventional and modern wound care, the comfort level of informants doing conventional and modern wound care, the expectations of the informant's family doing conventional and modern wound care, and supporting systems (supporting family) informants carry out conventional and modern wound care.